Zum programmatischen Potenzial des Schulprogramms - Markewitz, Friedrich (Schulprogramme Höherer Lehranstalten. Interdisziplinäre Perspektiven auf eine wiederentdeckte bildungs- und kulturwissenschaftliche Quellengattung)

Wiederholung. Zu einem temporalen und ästhetischen Muster passiv erfahrener Zeit in feuilletonistischen Städtebildern Siegfried Kracauers. - Öhlschläger, Claudia (ZfdPh, Heft 2/2021)

Digitale Zugänge zu kommunikativer Praxis schaffen: Eine explorative Interviewstudie im Projekt Sprachbegleitung Geflüchteter - Can, Magdalena; Müller, Mareike; Niederhaus, Constanze (Lockdown, Homeschooling und Social Distancing – der Zweitspracherwerb unter akut veränderten Bedingungen der COVID-19-Pandemie)
Aufgrund der Einschränkungen im Rahmen der COVID-19-Pandemie sind viele Geflüchtete von Zugängen zur Aneignung der deutschen Sprache und damit von gesellschaftlicher und bildungsbezogener Teilhabe abgeschnitten. Die vorliegende Untersuchung erkundet, inwiefern das bislang präsenzbasierte Projekt Sprachbegleitung Geflüchteter pandemiebedingt auch digital vermittelte Zugänge zu Interaktions- und Sprachlerngelegenheiten schaffen und so die Auswirkungen der gesellschaftlichen und bildungsbezogenen Isolation für Geflüchtete in Gemeinschaftsunterkünften abmildern kann. Aufbauend auf einer Fragebogenuntersuchung werden dazu die Erfahrungen und Sichtweisen drei afghanischer bzw. iranischer Geflüchteter mittels episodischer Interviews elizitiert und im Rahmen einer qualitativen Inhaltsanalyse ausgewertet. Damit wird explorativ erforscht, welche Grenzen und Chancen digitaler Zugänge zu Interaktion und kommunikativer Praxis sich skizzieren lassen und welche Konsequenzen sich für die Gestaltung von Sprachlern- und Partizipationsmöglichkeiten für Geflüchtete ableiten lassen.

Vom ‚Komaglotzen‘ zum literar- und medienästhetischen Lernen. Konzeptualisierung eines fernsehseriellen Lehr-Lern-Settings am Beispiel des Teen Dramas ANNE WITH AN E. - Kißling, Magdalena (Der Deutschunterrich (2))

Intermedialer Literaturunterricht. Ein medienintegratives Differenzierungskonzept zur Förderung literarästhetischen Lernens am Beispiel ausgewählter Kinderromane für die Sekundarstufe I - Kißling, Magdalena (Medienwissenschaften und Mediendidaktik im Dialog – Zum Status Quo von Medienbildung im Deutschunterricht)

Einleitung - Kißling, Magdalena (Kinder- und Jugendliteratur intermedial. Unterrichtsanregungen und -materialien zum literarischen Lernen im Medienverbund anhand von Emil und die Detektive (Gym/Ge) und Jakob der Lügner (BK). Erstellt von Masterstudierenden der Universität Paderborn)

Passivität als Widerstand gegen die Macht der Verhältnisse? "Bartleby, the scrivener" aus literaturwissenschaftlicher und ökonomischer Perspektive - Öhlschläger, Claudia; Schneider, Martin (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Die Bedeutung von Intertextualität für die Beschreibung der historischen Textsorte Schulprogramm. Zu Text-Text- sowie Text-Textwelt-Beziehungen - Markewitz, Friedrich (Intertextualität. Vom Zitat zur Anspielung in Texten der deutschen Sprache vom 8. bis zum 19. Jahrhundert)

Umsetzbarkeit des Wortschatzsammler-Therapiekonzepts bei Kindern mit Trisomie 21. Eine qualitative Einzelfallstudie - Glowania, M; Lassmann, I; Ulrich, Tanja (Praxis Sprache)

Kasusfähigkeiten mehrsprachiger Achtjähriger. Eine explorative Pilotstudie in Regelgrundschulen - Ulrich, Tanja; Thater, S; Mennicken, S (Logos)

Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas

Gattung und Geschlecht. Weibliche Tragödienheldinnen in Lessings Emilia Galotti? - Süwolto, Leonie (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas)

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie (blog interdisziplinäre geschlechterforschung)

Topographien der Vergänglichkeit. Vanitas, Alter und Gesellschaft bei Monika Maron und Martin Walser - Süwolto, Leonie (Vanitas und Gesellschaft)

Einleitung - Schlieper, Hendrik (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Genealogische Spuren in Racines Phèdre - Schlieper, Hendrik (Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft)

Helden-Geschlechter: Die Bérénice-Tragödien Corneilles und Racines - Schlieper, Hendrik (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas. (culturae, 21))

Tendres conquêtes: l’Amérique galante selon Rameau et Fuzelier (Les Indes galantes, 1735) - Schlieper, Hendrik (Amérique(s) poétique(s) entre Ancien et Nouveau Monde. L’espace américain comme nouveau territoire de la fiction de Fontenelle à Chateaubriand. Révolutions et Romantismes, 27))

Gattung und Geschlecht: Überlegungen zu einem kulturstiftenden Paradigma - Schlieper, Hendrik (Gattung und Geschlecht. Konventionen und Transformationen eines Paradigmas)

Sophonisbe: alea et agôn, genre tragique et gender. Les en-jeux diversifiés de la politique et de l’amour - Schlieper, Hendrik (Corneille présent, 1)

Komparatistik heute. Aktuelle Positionen der Vergleichenden Literatur- und Kulturwissenschaft

James Bond - mit Vergil gesehen: "Dr. No" (1962) - Steigerwald, Jörn (Komparatistik heute. Aktuelle Positionen der vergleichenden Literatur- und Kulturwissenschaft)

La tragedia amorosa dell'"Adone" ossia il nuovo ordinamento dell’amore - Steigerwald, Jörn (L’“Adone“ di Giovan Battista Marino. Mito - Movimento - Maraviglia. Atti del convegno internazionale (Humboldt-Universität zu Berlin, 1-2 luglio 2019))

Corneille maître du jeu ou la dramatologie novatrice de „Rodogune" - Steigerwald, Jörn (Corneille présent n° 1, 2021, Corneille: un théâtre où la vie est un jeu)

Von der Liebestragödie zur Tragödie der Liebe: Jean Racines „Phèdre" - Steigerwald, Jörn (Literaturwissenschaftliches Jahrbuch 62)

Erklärtexte lesen und schreiben. Praxis Deutsch 285

Textprozeduren und der Erwerb literaler Kompetenz - Rezat, Sara; Feilke, Helmuth (Sprach(en)erwerb. Der Deutschunterricht. Koch, Nikolas/Kozikowski, Barbara (Hrsg.))

Zur makrostrukturellen Prägung argumentierender Textprozeduren - Rezat, Sara (ar|gu|men|tie|ren. Eine zentrale Sprachhandlung im Fach- und Sprachunterricht)

Digitale Desinformation und Fake News. Schülerinnen und Schüler erklären, warum Fake News sich so gut verbreiten - Rezat, Sara; Arnold, Cynthia (Praxis Deutsch 285)

Erklärtexte lesen und schreiben. Basisartikel - Rezat, Sara; Feilke, Helmuth (Praxis Deutsch 285)

Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020

Die Landstraße jenseits der Bedeutung. Peter Handkes spätes Drama Die Unschuldigen, ich und die Unbekannte am Rand der Landstraße - Famula, Marta (Literatur und Kultur zwischen West und Ost. Imagination, Kommunikation und Wahrnehmung in regionalen Kulturräumen. Festschrift für Paul Martin Langner zum 65. Geburtstag)

Von der auf den Kopf gestellten Schönheit oder die Verneinung der Negation im Hässlichen. Zur dialektischen Funktion des Erhabenen und des Hässlichen bei Christian Hermann Weiße - Famula, Marta (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung)

Vom Entschluss, die Welt zu bestehen. Dürrenmatts Ethik des ‚à la bande‘ - Famula, Marta (Kosmos Dürrenmatt. Eine Annäherung an den Denker, Dichter und Maler. Berner Zeitschrift für Geschichte, H. 3. Sonderdruck Spiezer Tagung, in: Annelise Hüssy, Stefanie Leuenberger (Hgg.))

Ästhetik im Vormärz – Zur Einführung - Famula, Marta; Otto Eke, Norbert (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020)

Lukas Bärfuss: Malinois. Erzählungen. Wallstein: Göttingen 2019 - Famula, Marta (Jahrbuch für internationale Germanistik, Jahrgang LIII – Heft 1 (2021))

Das Unveränderliche und die Wiederholung. Die Rolle der Kontingenz in Max Frischs letztem Drama Triptychon - Famula, Marta (Wiederholung im Theater. Zur deutschsprachigen Gegenwartsdramatik und ihrer Inszenierung, (= Gesellschaftskritische Literatur – Texte Autoren – Debatten 9))

Drama zwischen Text und Bühne (Schriftenreihe seit 2021)

Orthografieunterricht heute. Theorie – Empirie – Didaktik

Das ,rechte Schreiben‘ lernen. Von der Buchstabiermethode zur sprachsystematischen Vermittlung - Köller, Katharina; Tophinke, Doris (Der Deutschunterricht)

Zur Wirkung der universitären DaZ-Weiterbildungen an den Standorten Duisburg-Essen, Münster und Paderborn. Auswertung von schriftlichen Reflexionen teilnehmender Lehrkräfte - Asmacher, Judith; Borowoski, Damaris; Böttger, Lydia; Islinger, Günter; Robers, Christin (Universitäre Weiterbildungen im Handlungsfeld von Deutsch als Zweitsprache)

Brand names as multimodal constructions. On the role of typography as an additional indicator of onymisation. - Dübbert, Alexander (Linguistics Vanguard)
Brand names are a common part of the everyday consumer environment, and can be found on countless visual surfaces such as food packaging. A key characteristic of brand names is their fixed design. Many brand names owe their linguistic form to units that originally did not constitute proper names. They developed into brand names through complex sub-processes of what is commonly referred to as onymisation. These processes include semantic, morphological and phonological/graphemic changes. The aim of this paper is to explore how the specific typographic design of a brand name can be an additional indicator in its process of onymisation. After clarifying the concepts of onymisation and typographic design, an extended multimodal construction model is presented. The basis of the paper is an analysis of a corpus of image data comprising more than 600 photographs of food packaging. In order to get a first impression of how the multimodal constructions of brand names could look, an omission test following a suggestion by Ziem (2017) is applied to the data.

Angstkonstruktionen zwischen „sinnvoller Vorsicht und sinnloser Panik“ - Georgi, Christopher (Angstkonstruktionen)

Digitally Assessing Text Comprehension in Grades 3-4: Test Development and Validation - Seifert, Susanne; Paleczek, Lisa (Electronic Journal of e-Learning)
A prerequisite for child reading support at school is adequate assessment. Embedding (repeated) assessment into daily teaching routine is often challenging for teachers in terms of time and organization. The use of digital tools can help teachers in the assessment process (in preparation, evaluation, documentation, etc.). A digital assessment tool (Graz Reading Comprehension test: GraLeV), focusing on assessing reading comprehension skills in Grades 3 and 4 is currently being developed in Austria. This reading assessment covers reading comprehension at the word, sentence, and text level. Text level is assessed via two subtests (Subtest I: presentation of nonsense-stories and corresponding questions, and Subtest II: maze selection). The other levels consist of one subtest each. This paper focusses on the subtests at text level. More specifically, the paper reports the results of two studies. Study 1 describes the development phases and the first piloting of these two subtests (data collection: 10/2019-12/2019). Testing 273 students with preliminary versions of the subtests (Subtest I: 30 items, Subtest II: 60 items) produced information on (a) item difficulty, (b) item discriminatory power, and (c) time limits for future speed testing. Items not meeting the required quality criteria were excluded. The final version of Subtest I consists of 16 questions referring to eight different, short, nonsense-texts. Its testing time (without instructions) is three minutes. The final version of the Subtest II consists of 2 texts each with 15 maze selections (30 items) and testing time is 100 seconds. The internal consistency is found to be good for Subtest I (α=.87) and Subtest II (α=.78 to .80). Study 2 reports on testing for validity and retest-reliability (data collection: 09/2020-11/2020). Student scores in another reading comprehension test, together with teacher assessments of reading comprehension, were used to assess congruent validity. Divergent validity was assessed using teacher assessments of mathematical and socio-emotional skills. As expected, the correlations with the congruent measures were higher than those with the divergent measures. A subsample was tested twice with the GraLeV. Retest-reliability was acceptable for Subtest II. However, the scores obtained at time 2 were higher compared to those at time 1 in both subtests. This is probably the result of increased student familiarity with the digital device and the digital test environment at time 2. The results are discussed in the light of teachers’ needs for standardized digital assessments in order to facilitate the tailoring of student reading support.
Keywords: Computer Science Applications; Education

Is Reading Comprehension Taken for Granted? An Analysis of Austrian Textbooks in Fourth and Sixth Grade - Seifert, Susanne (Technology, Knowledge and Learning)
Abstract The range of teaching materials now available is becoming increasingly diverse. Despite this, however, the use and influence of textbooks in teaching still remains very high. When instructing reading comprehension, teachers often use textbooks as the basis for teaching in language lessons. Establishing a good match between textbooks and the skills to be acquired is therefore essential. In this paper, I investigate whether textbooks used in Austrian schools can adequately support the teaching of reading comprehension skills. Since reading comprehension is the basis for acquiring knowledge in all subjects, science textbooks are examined in addition to (German) language lesson textbooks. Thus, the content pages of four language textbooks and four science textbooks for fourth and sixth grade were analysed in terms of five different categories, i.e. general structural setup, learning goals, text types, text structures, and activities. The results reveal clear variations with respect to learning goals in language textbooks. For example, the extent to which reading comprehension is addressed ranges from 13.64 to 69.70%, depending on the book used. Although not addressed as a learning goal in the science textbooks, reading comprehension is often presupposed, especially in sixth grade. While the instruction of reading comprehension ought to entail coverage of reading strategies, this is often neglected, or only dealt with indirectly. Given the diversity of textbooks analysed, it seems all the more important to stress that teachers should: 1) clarify the goals and teaching strategies of a book before using it, 2) become aware of strategies that support the development of students' reading comprehension, and 3) use textbooks as a complementary (and not sole) tool to support reading comprehension in all subjects.
Keywords: Computer Science Applications; Human-Computer Interaction; Education; Mathematics (miscellaneous)

The presence of students identified as having special needs as a moderating effect on their classmates’ reading comprehension scores in relation to other major class composition effects - Krammer, Mathias; Seifert, Susanne; Gasteiger-Klicpera, Barbara (Educational Studies)
Keywords: Education

Comparing digital to print assessment of receptive vocabulary with GraWo‐KiGa in Austrian kindergarten - Paleczek, Lisa; Seifert, Susanne; Schöfl, Martin (British Journal of Educational Technology)
Keywords: Education

Teaching and learning in a multilingual Europe: findings from a cross-European study - Dockrell, J. E.; Papadopoulos, T. C.; Mifsud, C. L.; Bourke, L.; Vilageliu, O.; Bešić, E.; Seifert, Susanne; Gasteiger-Klicpera, B.; Ralli, A.; Dimakos, I.; Karpava, S.; Martins, M.; et al. (European Journal of Psychology of Education)
Abstract School classrooms within the EU are multilingual learning environments. The diversity of pupils in classrooms raises significant challenges for teachers, but to date, there are no data from large-scale surveys that compare views within and across European countries. A bespoke questionnaire was designed to examine views of current classroom learning environments with respect to the multilingualism. The questionnaire was piloted and subsequently completed by 2792 teachers across different European countries. Eleven countries provided sufficient data for analyses. Results from structural equation modelling showed that teachers’ attitudes could be reliably measured across Europe with the use of carefully devised questionnaire, whose loading and factor structure remained invariant across countries. Teachers’ views about multilingualism were most challenged by the numbers of children in their classes, not the percentage of multilingual pupils in the class. Countries differed in how they perceived multilingualism, with their differences leading to distinctive country clusters. Gender and education level (elementary vs. secondary) differences were also observed irrespective of country. These findings enhance our understanding of the role that the characteristics of teachers and their classrooms play in a multilingual setting across diverse European settings. The practical relevance of the results and new opportunities for teacher training are discussed.
Keywords: Developmental and Educational Psychology; Education

Moderne Heldin im antiken Gewand? Anne Webers „Annette, ein Heldinnenepos“ - Süwolto, Leonie

Zeit als Widerfahrnis. Ästhetik und Figuration passiv erfahrener Temporalität - Öhlschläger, Claudia; Roselli, Antonio (ZfdPh)